2011
DOI: 10.3945/ajcn.111.016600
|View full text |Cite
|
Sign up to set email alerts
|

Intake of fruit, vegetables, and carotenoids in relation to risk of uterine leiomyomata

Abstract: Background: US black women have higher rates of uterine leiomyomata (UL) and lower intakes of fruit and vegetables than do white women. Whether fruit and vegetable intake is associated with UL in black women has not been studied. Objective: We assessed the association of dietary intake of fruit, vegetables, carotenoids, folate, fiber, and vitamins A, C, and E with UL in the Black Women's Health Study. Design: In this prospective cohort study, we followed 22,583 premenopausal women for incident UL (1997UL ( -20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 79 publications
(78 reference statements)
4
101
2
5
Order By: Relevance
“…Previous data suggest a reduced risk of LMA among women with a greater dietary intake of fruit and preformed vitamin A (Wise, 2011) but this result was not repeated in this study.…”
Section: Discussioncontrasting
confidence: 89%
“…Previous data suggest a reduced risk of LMA among women with a greater dietary intake of fruit and preformed vitamin A (Wise, 2011) but this result was not repeated in this study.…”
Section: Discussioncontrasting
confidence: 89%
“…The study showed no association with isoflavones, consistent with two subsequent studies of soy intake (measured by food frequency questionnaire) and UL risk [110, 120], even in populations where soy intake was high [110]. Lignans, found in fruits and vegetables, were associated with a lower risk of UL in TULEP, consistent with results from the Italian case-control study [111] and the BWHS [118]. …”
Section: Etiologic Hypotheses and Risk Factorssupporting
confidence: 86%
“…Subsequently, several studies on diet and UL have been published in which validated food frequency questionnaires or nutrient biomarkers were used. The BWHS found that higher intakes of fruits and vegetables was associated with a reduced risk of UL [118]. In a subset of participants from The Uterine Leiomyomata Epidemiology Project (TULEP), urinary isoflavones and lignans were measured as biomarkers of soy intake [119].…”
Section: Etiologic Hypotheses and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some data suggest that fibroid growth differs by race, especially as women approach menopause (12). Although some evidence links environmental factors such as diet and history of abuse to this increased risk, most of this information comes from studies such as the Black Women's Health Study (1214). A recent study has linked vitamin D insufficiency with increased fibroid risk in black women (15).…”
Section: Biologic Studies Of Racial Differencesmentioning
confidence: 99%